Controlling inventory by improving demand forecasting within the alcoholic beverage industry : a case study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Logistics and Supply Chain Management at Massey University, Auckland, New Zealand - Deng, Xiaomu (Massey University, 2011)
This thesis explores how combing statistical demand forecasting methods and causal forecasting methods with judgmental forecasts via a Sales and Operation Planning process can improve inventory control through improving inventory replenishment strategies within an Australian alcoholic beverage importer and distributor. The implementation of a Sales and Operation Planning process has enabled the company to involve all necessary functions of the company in the demand forecasting and requirement planning process and in this way improve the balance of inventory between demand and supply. The implementation of the improved inventory management strategies and Sales and Operation Planning process is described here-in. The constantly evolving process of the Sales and Operation Planning process and the four stages of the process development are also described. The key demand and supply performances before and after implementation of new processes are measured. The results demonstrate a significant improvement in demand forecasting accuracy as well as improved inventory efficiency and customer service levels.
Keywords: Supply and demand forecasting; Sales and operation planning; Inventory control; Alcoholic beverage industry